2016
DOI: 10.1021/acs.energyfuels.5b02472
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Optimal Solvent Type for High-Temperature Solvent Applications in Heavy-Oil and Bitumen Recovery

Abstract: The selection of the most suitable solvent for an efficient heavy-oil recovery process is a critical task. Low carbon number solvents yield faster diffusion, but the mixing quality may not be high. Also, high carbon number solvents yield a better quality mixing (much less asphaltene precipitation), but the mixing process is rather slow. Hence, the understanding of solvent selection criteria for solvent-aided recovery processes has established two main aspects of oil−solvent (liquid−liquid) interaction:(1) oil−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Some researchers have studied the mechanism of warm VAPEX. Marciales and Babadagli 21 reported that the selection of the most suitable solvent is a critical task for an efficient warm VAPEX process. Oil–solvent mixture quality and rate of mixture formation solvent are two main selection criteria for solvent-aided recovery processes.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have studied the mechanism of warm VAPEX. Marciales and Babadagli 21 reported that the selection of the most suitable solvent is a critical task for an efficient warm VAPEX process. Oil–solvent mixture quality and rate of mixture formation solvent are two main selection criteria for solvent-aided recovery processes.…”
Section: Introductionmentioning
confidence: 99%
“…The solubility of CO 2 in heavy oil is 50-100 m 3 /m 3 at 6.0 MPa, and the volume expansion of crude oil is 10-20%, which reduces the oil viscosity by more than 80% [33,34]. Moreover, CO 2 is highly soluble in the asphaltene components, which can further enhance oil recovery [35]. However, the sweep efficiency is relatively low when only CO 2 is injected [36].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the effects of phase behaviour on the SA-SAGD performance has been studied by Khaledi et al concluding that a multicomponent hydrocarbon solvent may be used to significantly improve efficiency 23 . Marciales and Babadagli have also investigated the selection of optimal solvent discussing the need to find a compromise between low carbon number solvents that result in faster diffusion and high carbon number solvents that yield better mixing qualities but slower mixing 24 . However, the concepts of thermal-solvent recovery in fractured reservoirs has not been successfully modelled yet.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, studies have been conducted to explore solutions for heavy oil recovery from this type of reservoir over the last couple of years. Experimental studies have shown that hot solvent techniques have the potential to improve heavy oil recovery from fractured reservoirs but gave limited insight into the mechanisms that operate. ,, Pathak et al injected hot solvents into a cylinder containing preserved bitumen saturated cores (from the Grosmont formation) which were in contact with the solvent on all sides representing a matrix-fracture element of a fractured reservoir . The solvent was allowed to soak into the core diluting the bitumen, then the mixture was collected from beneath the core.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation